Plaatje's African romance: the translation of tragedy in Mhudi and other writings - Walter, Brian Ernest (Rhodes University, Faculty of Humanities, Department of Literary Studies in English, 2001)
This study brings together Plaatje's politicaland literary visions, arguing that the one informs the other. Plaatje's literary work is used as a starting point for the discussion, and the first chapter explores the relationship of his political and artistic visions. Mhudi is his definitive romance text, and it is argued that Plaatje's romance visionin this text is reflected in his political thinking, and in turn reflected by it. His romance work was part of a literary romance tradition which Plaatje both drew upon and transformed, and thus the basic features of romance are explored in Chapter Two. Plaatje's work is situated between two influential romance models, therefore Chapter Two also discusses the romances of Shakespeare, whomPlaatje read as reflectinga non-racial humanism that was translatable into the African context, in terms of political vision and of literary text. His other models were the colonial romances of Haggard. It is argued that, while Plaatje could glean many elements fromHaggardthat suited his purposes as an African, specifically a SouthAfrican, writer, he nevertheless"”despite his own pro-British leanings, qualified though they might have been by the complexities of his colonial context"”would not have represented Africa and Africans in terms of the exotic other in the way Haggard clearly did. Thus Plaatje, in terms of his romance vision, may have usedmanyofthe themesand techniques of Haggardianromance, but consistently qualified these colonial works by using the more classically shaped Shakespearean romance structure at the deep level of his work. The third chapter examines Haggard's romance, but differentiates between two Haggardian types, the completed or resolved romance, whichis more classical in its form, and evokes an image of a completed quest, as well as the necessity of the quester entering the world again. Haggard's "completed" African romance, it is argued, is resolved only in terms of a colonial vision. Chapter Four, by contrast, examines examples of his unresolved African romance, in which African ideals implode, and show themselves to be inneed of foreign intervention. It is argued that Haggard's image of Africa was based on the unresolved or incomplete romance. His vision of Africa was such that it could not in itself provide the materialfor completed romance. This vision saw intervention as the only option for South Africa. While Plaatje uses elements of Haggard's "incomplete" romance models when writing Mhudi, he handles both his narrative and politicalcommentaryin this text in terms of his own politicalthought. This non-racial politicalvisionis guided by his belief that virtue and vice are not the monopoly of any colour, a non-racialism he associates with Shakespeare. However, within the context of the South Africa of his fictionand of his life, this non-racial ideal is constantly under threat. It is partly threatened by political forces, but also challenged by moral changes within individuals and societies. In Chapter Five the examination of Plaatje's work begins withhis Boer War Diary, inwhicha romance structure is sought beneath his diurnal observations and political optimismduring a time of warfare and siege. The discussion of this text is followed by a reading of Native Life in South Africa in which it is argued that Plaatje looks, in the midst of personal and social suffering, for that which can translate a tragic situation into romance resolution. "Translation" is used in a broad sense, echoing Plaatje's view of the importance of translation for cross-cultural understanding and harmony. The arguments of Chapter Five are extended into Chapter Six, where a reading of Mhudi places emphasis on the possibilities of change implied in romance. Plaatje's non-racial humanism recognizes the great potential for injustice and human suffering within the context of South African racism, but constantly seeks to translate such suffering into the triumph of romance. While the narrative of Mhudi concludes on a romance peak, tensions between the tragic and romance possibilities alert the reader to the sense that, despite its romance resolution, something has been lost in the translation of the potential tragedy into romance.
Keywords: Plaatje, Sol. T. (Solomon Tshekisho), 1876-1932 -- Mhudi; Race in literature; Politics in literature